Experimental and numerical investigation of flow and thermal effects on flexible printed circuit board. (May 2017) - Lim, C.H.; Abdullah, M.Z.; Azid, I.A.; Abdul Aziz, M.S.
Abstract: The desire of flexibility, compact, lightweight and low cost in current electronic device increases the application of flexible printed circuit board (FPCB). However, FPCB would encounter significant deflection and stress under operating condition (thermal factor) with air flow cooling system as compared to rigid printed circuit board (RPCB). Therefore, present study aims to investigate the effects of airflow rate and heat on FPCB attached with a ball grid array (BGA) package using experimental and numerical method. In this present study, the simulation was carried out by using FLUENT and ABAQUS, coupled in real time by Mesh-based Parallel Code Coupling Interface (MpCCI) where flow and thermal effects were coupled simultaneously. The experiments were conducted in a wind tunnel with the BGA package on the FPCB. Low discrepancy between simulation and experimental results indicated that the proposed numerical simulation method is proven to be reliable and sufficient to study the FPCB with thermal and flow effects which has not been established by previous researchers. The findings also showed that the Reynolds number and heat have significant effects on FPCB's deflection and stress. Therefore, it is important to include thermal effect when dealing with FPCB under flow environment. The outcomes of this paper can be a guideline to the FPCB industries. Highlights: Development of thermal-mechanical-fluid-structure interaction numerical coupling method Thermal and flow effects on FPCB with BGA packages attached in flow environment has been investigated. Findings show that cases with thermal effect has inverse and larger trend line as compared with cases without thermal effect.